Does Hyperdense Middle Cerebral Artery Sign Predict the Prognosis of Patients Undergoing Emergency Endovascular Treatment? - Wang, Pian; Fan, Jin; Wang, Weiping; Chen, Yangmei (Current neurovascular research, 2025)
Hyperdense Middle Cerebral Artery (HMCAS) is one of the early CT signs of acute Ischemic Stroke (AIS) in patients with large vessel occlusion (LVO). Whether HMCAS is an accurate predictor of functional outcomes in LVO-AIS patients still needs to be further studied. The aim of this study was to analyze the predictive ability of HMCAS on functional outcomes in LVO-AIS patients who underwent emergency endovascular treatment with or without intravenous thrombolysis (IVT). The clinical and imaging data in LVO-AIS patients who underwent emergency endovascular treatment with or without IVT were retrospectively analyzed. The patients were divided into HMCAS+ group and HMCAS- group according to the presence or absence of HMCAS on initial CT. The endpoint was the 90-day Modified Rankin Scale (mRS) and multivariate logistic ordinal regression was used to determine the association between the presence of HMCAS and 90-day mRS. A total of 173 middle cerebral artery (MCA) LVO-AIS patients were recruited for this study, with 69 (39.88%) in the HMCAS+ group and 104 (60.12%) in the HMCAS- group. The mean age of the participants was 68.98±13.529 years, with 89 (49.71%) being male and 67 (38.73%) receiving intravenous thrombolysis. Multivariate logistic regression of the presence of HMCAS (OR, 1.240 95% CI, 0.693-2.219 P =0.511) was not significantly associated with the 90-- day mRS score. HMCAS may not be a predictor of 90-day mRS in MCA LVO-AIS patients. However HMCAS+ group patients had higher stroke severity before IVT and emergency endovascular treatment. In the era of emergency endovascular treatment the factors affecting the prognosis of LVO-AIS may be different from those of the past.